Exfoliated carbon nitride nanosheets decorated with NiS as an efficient noble-metal-free visible-light-driven photocatalyst for hydrogen evolution1. Issue 26 (14th July 2015) - Lu, Yongtao; Chu, Dongmei; Zhu, Mingshan; Du, Yukou; Yang, Ping
<x xml:space="preserve">Abstract</x> Exfoliated ultrathin C3N4 nanosheets decorated with NiS as a highly efficient visible-light-driven photocatalyst for photoinduced hydrogen evolution.